Planning for Planet or City? - Davidson, Mark (2016)
If we now live with a planetary urban process (Brenner & Schmid, 2015a), the very idea of “future cities” must be brought into question. Indeed, we might ask whether urban planning has morphed into planetary planning, with its primary charge being the construction of vast networks of urban systems coordinating a global capitalist process. This commentary cautions against such over-extended theories of urbanization and related planning practices. Although global capitalism has engendered profound spatial changes, the concept of the city remains a crucial social and political idea. By outlining the continued centrality of the city to social and political life, the commentary argues for a democratic evaluation of the urban form in order to plan for, and realize, more just cities.